2010
DOI: 10.1017/s0960258509990249
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal nature of seed responses to fluctuating temperatures in Cynara cardunculus (L.)

Abstract: Cynara cardunculus (L.) seeds require incubation at fluctuating temperatures to terminate dormancy. In this study, we analysed the physiological mechanisms underlying such a requirement, focusing on the role of abscisic acid (ABA) and gibberellin (GA). As a conceptual framework, we considered the possibility that fluctuating temperatures and light trigger a similar set of hormonal processes after stimulus perception. To test this possibility, we (1) carried out hydrotime analysis of germination in seeds expose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
38
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 36 publications
5
38
0
Order By: Relevance
“…Huarte and Benech-Arnold (2010) found that exogenous GA 3 could entirely substitute for temperature fluctuation for C. cardunculus seed germination. This suggests that temperature fluctuation may increase GA biosynthesis during imbibition and increase embryo growth potential to overcome physical constraint.…”
Section: Seed Germination and Dormancy Response To Temperaturementioning
confidence: 98%
See 2 more Smart Citations
“…Huarte and Benech-Arnold (2010) found that exogenous GA 3 could entirely substitute for temperature fluctuation for C. cardunculus seed germination. This suggests that temperature fluctuation may increase GA biosynthesis during imbibition and increase embryo growth potential to overcome physical constraint.…”
Section: Seed Germination and Dormancy Response To Temperaturementioning
confidence: 98%
“…Many studies (Chen et al 2009;Baskin and Baskin 2004) have shown that ABA is one of the most important inhibitors of seed germination. Huarte and Benech-Arnold (2010) reported that fluctuating temperature significantly reduced embryo sensitivity to ABA, and possible contributed to dormancy release. Results of the present study showed that an ABA inhibitor, fluridone, significantly increased seed germination at 20/30°C, suggesting that ABA biosynthesis during imbibition play a critical role in seed dormancy maintenance (Baskin and Baskin 2004).…”
Section: Seed Germination and Dormancy Response To Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…We combined germination data from the range of experimental Ψ treatments and used equation 2 to predict and plot germination [34]. Following Huarte and Benech-Arnold [35], we used the Solver tool of Microsoft Excel (2003–2010) to derive parameters for this function by minimizing the root-mean-square error (RMSE) between simulated and observed data. ANOVA was conducted for each parameter and protected LSD (P<0.05) values obtained using JMP 8.0 software (SAS Institute Inc. Cary, NC); orthogonal contrasts of means were subsequently used to compare between R and S groups of populations.…”
Section: Methodsmentioning
confidence: 99%
“…sylvestris seeds display an almost absolute requirement for fluctuating temperatures for dormancy termination. Indeed, studies in C. cardunculus (L.) have shown that fluctuating temperatures terminate dormancy by reducing ABA content and sensitivity (Huarte and Benech-Arnold, 2010). This implies that fluctuating temperatures terminate dormancy in this species through an enhancement of embryo potential to overcome a physical restraint for germination.…”
Section: Introductionmentioning
confidence: 99%